2009
DOI: 10.1021/jp8109034
|View full text |Cite
|
Sign up to set email alerts
|

Surface Adsorption and Aggregate Formation of Cationic Gemini Surfactant and Long-Chain Alcohol Mixtures

Abstract: We measured the surface tension of aqueous solutions of octanol-butandiyl-1,4-bis(decyldimethylammonium bromide) using the drop-volume technique at 298.15 K under atmospheric pressure as a function of the total molality and bulk composition. The results of the surface tension measurements, which were analyzed by originally developed thermodynamic equations, suggested that octanol molecules filled the spaces among the hydrophobic chains of gemini surfactants and formed a densely packed monolayer with them in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Therefore, DDA, ether amine and AC1201 and their protonation species had difficulty forming a covalent bond with the silicon atom on the mineral surfaces, which agrees well with previous studies (Matsubara et al, 2009;Chernyshova et al, 2000;Fuerstenau and Jia, 2004). According to classical chemical theory, all chemical interactions are by either electrostatic or orbital.…”
Section: Dft Calculation Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, DDA, ether amine and AC1201 and their protonation species had difficulty forming a covalent bond with the silicon atom on the mineral surfaces, which agrees well with previous studies (Matsubara et al, 2009;Chernyshova et al, 2000;Fuerstenau and Jia, 2004). According to classical chemical theory, all chemical interactions are by either electrostatic or orbital.…”
Section: Dft Calculation Resultssupporting
confidence: 90%
“…Characteristic of the organic function ether C-O, reagents belonging to this class are known as ether amines which are widely used in industry nowadays (Araujo et al, 2005). The mechanism of amine-silicate interaction has been studied extensively by flotation recovery response (Novich and Ring, 1985), adsorption experiments (Matsubara et al, 2009;Zhou and Somasundaran, 2009), atomic force microscope (AFM) (Zhang et al, 2007), contact angle (Fuerstenau and Jang, 1991), zeta-potential (Chernyshova et al, 2000;Fuerstenau and Jia, 2004) and FTIR spectroscopy (Chernyshova et al, 2001;Lima et al, 2004;Chernyshova and Rao, 2001a,b) in the last several decades. There is a general consensus that the mechanism of amine adsorption on silicate depends on pH and collector concentration.…”
Section: Introductionmentioning
confidence: 99%
“…These results apparently indicate that the addition of alcohol promoted the formation of a more densely packed monolayer in comparison to that of 12-2-12 alone, agreeing with the role of linear alcohols in other surfactant systems. [21][22][23][24][25] Moreover, the C 7 OH had higher efficiency than the C 6 OH. For example, at a comparable concentration of 4.0 mmol L À1 of alcohol, the G t,tails was 6.21 mol cm À2 for C 7 OH and 5.39 mol cm À2 for C 7 OH, respectively (Table 1).…”
Section: Synergistic Effect and Mixed Adsorption Of 12-2-12/ Alcohol ...mentioning
confidence: 99%
“…Many authors have studied the interactions of alcohols with ionic surfactants (including ionic gemini surfactants) and concluded that linear alcohols effectively promoted the ionic surfactant to form a dense adsorption monolayer. [21][22][23][24][25] However, to our knowledge, none of these studies focused on the relationship between foam stability and system composition. This work rst reports highly stable foams generated in the mixed systems of a gemini surfactant with a short spacer (12-2-12) and hexanol (C 6 OH) or heptanol (C 7 OH).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there is an increasing interest in novel forms of surfactants, particularly in dimeric or gemini surfactants, which consist of two conventional surfactants joined by a spacer at the head group, as they exhibit significant surface activity properties that cannot be achieved by conventional surfactants [1,2]. These improved properties may make them very useful in many applications, such as soil remediation, enhanced oil recovery, drug entrapment and release, and the construction of high-porosity materials [3][4][5]. Considerable effort has been put into the design and synthesis of a variety of gemini surfactants with the desired properties [6][7][8][9], and to understand the relationship between the architectures of gemini surfactants and their various surface activity properties in aqueous solution [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%